Daya Terima Masyarakat terhadap Shortcake Labu Kuning (Curcubita Moschata) sebagai Inovasi Makanan Penutup - Lucia Rasifa Anggira; Tri Rettagung Diana; U.Yuyun Triastuti (Garina, 2025)
This study focuses on the development of pumpkin shortcake (Curcubita moschata) as a dessert innovation, utilizing the potential of Indonesia’s local food resources, which are highly nutritious and widely available. Pumpkin is well known for its high dietary fiber content that supports digestion, as well as its antioxidant properties that may reduce the risk of cancer and chronic diseases. While traditional shortcakes are commonly made with strawberries, this innovation aims to substitute conventional ingredients with pumpkin, thereby not only enhancing nutritional value but also supporting the local farming economy. The main objectives of this research are to identify the production process and formulation of pumpkin shortcake, evaluate consumer acceptance of the product, and analyze packaging and presentation strategies that enhance consumer appeal. The production process involved selection, washing, steaming, and pureeing of pumpkin, followed by weighing, mixing, molding, baking, cooling, filling, and cutting. The third experiment successfully produced a product that met all sensory criteria, including color, taste, texture, and aroma. A hedonic test involving 35 untrained panelists indicated that pumpkin shortcake with 25% liquid milk and 75% pumpkin (Code 731) was the most preferred, particularly in terms of taste and color, while the 50% milk and 50% pumpkin formulation (Code 281) was most favored for aroma and texture. The findings conclude that the formulation of pumpkin shortcake with 25% liquid milk and 75% pumpkin is the most accepted by consumers. Attractive packaging and presentation are also emphasized as essential strategies to enhance product appeal and market value.